Machiavellianism, Impulsivity, and Empathy: Understanding Aggressive Driving Behavior - Rendy Alfiannoor Achmad; Silvia Kristanti Tri Febriana; Laily Maulida; Igha Ananda Saidah Muharram; Lili Aprilianti (Psympathic : Jurnal Ilmiah Psikologi, 2023)
This study aimed to investigate the impact of impulsivity, Machiavellianism, and empathy on the inclination towards aggressive driving behavior. A cross-sectional analysis was conducted, utilizing a sample size of 315 Indonesian drivers. Accordingly, the instruments used include Aggressive Driving Behavior Scale (ADBS), Short Version of the UPPS-P (SUPPS-P) Scale, Machiavellian Personality Scale (MPS) and Interpersonal Reactivity Index (IRI) Scale. The multiple linear regression results showed that impulsivity, Machiavellianism, and empathy significantly influenced the tendency toward aggressive driving behavior with F count of 12.454 and significance level of .000 < .05. Furthermore, the dimensions of impulsivity, lack of perseverance, and Machiavellianism, were observed to partially have an effect on the tendency toward aggressive driving behavior at .221 or 22.1%, which was categorized as moderate. It was also important to acknowledge that the other dimensions observed in this study had no significant effect on the subject matter.